1996
DOI: 10.1074/jbc.271.40.24781
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast Growth Factor-2 Binds to the Regulatory β Subunit of CK2 and Directly Stimulates CK2 Activity toward Nucleolin

Abstract: The presence of fibroblast growth factor-2 (FGF-2) in the nucleus has now been reported both in vitro and in vivo, but its nuclear functions are unknown. Here, we show that FGF-2 added to nuclear extract binds to protein kinase CK2 and nucleolin, a CK2 natural substrate. Added to baculovirus-infected cell extracts overexpressing CK2 or its isolated subunits, FGF-2 binds to the enzyme through its regulatory ␤ subunit. Using purified proteins, FGF-2 is shown to directly interact with CK2 and to stimulate CK2 act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
116
0
2

Year Published

1997
1997
2013
2013

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 143 publications
(119 citation statements)
references
References 46 publications
(46 reference statements)
1
116
0
2
Order By: Relevance
“…This interaction is mediated by the b regulatory subunit of CK2. Similar interactions with the b subunit have been reported for CK2-specific substrates: p53 (Filhol et al, 1992), FGF2 (Bonnet et al, 1996), DNA Topoisomerase IIa , CD5 (Raman et al, 1998), Nopp 140 (Li et al, 1997a) and the p21 protein (a CDK inhibitor) (Gotz et al, 2000;Romero-Oliva and Allende, 2001). It is clearly established that on binding to CK2b, CK2a changes activity and substrate specificity.…”
Section: Discussionmentioning
confidence: 62%
“…This interaction is mediated by the b regulatory subunit of CK2. Similar interactions with the b subunit have been reported for CK2-specific substrates: p53 (Filhol et al, 1992), FGF2 (Bonnet et al, 1996), DNA Topoisomerase IIa , CD5 (Raman et al, 1998), Nopp 140 (Li et al, 1997a) and the p21 protein (a CDK inhibitor) (Gotz et al, 2000;Romero-Oliva and Allende, 2001). It is clearly established that on binding to CK2b, CK2a changes activity and substrate specificity.…”
Section: Discussionmentioning
confidence: 62%
“…FGF-2 also regulates the serum response factor (SRF) promoter by two mechanisms involving either an ETS binding site or a Sp1 binding portion (Spencer et al, 1999). Furthermore, nuclear 24 kDa FGF-2 can interact with the protein kinase CK2 (Bonnet et al, 1996), the ribosomal protein L6/TaxREB107 (Shen et al, 1998b) and with the anti-apoptotic factor FIF (Van den et al, 2000). Several reports have suggested that CK2 is able to control transcription by phosphorylating transcription factors (Grein and Pyerin, 1999;Guo et al, 1999;Zhou et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…FGFs 1 and 2 might be released from damaged cells or by an exocytotic mechanism that is independent of the endoplasmic reticulum-Golgi pathway (Mignatti et al, 1992). It has also been reported that exogenously added FGF2 can be translocated to the nucleus where it can interact with and activate nuclear targets (Bonnet et al, 1996;Bailly et al, 2000). However, the physiological significance of FGF2 action in the nucleus remains unclear.…”
Section: Identification Of the Mouse Fgf Gene Familymentioning
confidence: 99%